Pengaruh Persentase Pertukaran Air pada Pertumbuhan Gracilaria verrucosa dalam Budidaya Bak Terkontrol [The Effect Of Percentage Water Replacement On Growth Of Gracilaria verrucosa In Controllable Tanks] - Rr. Juni Triastuti; Raindra Daksina; Rochmah kurnijasanti (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
AbstractGracilaria is a species of red algae which has potentially to culture. Generally, the culture is done in ponds, but today some ponds are use for housing and the pond number are decreasing, and the other hand the water quality of ponds is contaminated by industrial wasted. To overcome these problems, the solution is doing culture in a controllable tanks, no large space is needed, it can do in house, no seasonal influences and the supporting factors like o onutrient, pH, light intensity, temperature (C), salinity (/ ) and water circulation are easily to control. The purpose of oo this research is to determine the effect of water replacement on growth and the total number of chlorophyl a on Gracilaria verrucosa. This research was held at June 19 th 2009 – July 22 th 2009 in Laboratorium Kering, Fakultas Perikanan dan Kelautan and as the comparison is Desa Pulukerto Kecamatan Kraton, Kabupaten Pasuruan, Jawa Timur. The growth measurement in Public Health Veteriner Departement Faculty of Medical Veterinary Airlangga University Surabaya. The chlorophyll a measurement was held in Patology Clinic Departement Faculty of Medical Veterinary Airlangga University Surabaya. This research use Fully Randomized Design method with 5 treatments : in treatment A there was no water replacement (0%), in treatment B the replacement was 25%, replacement in treatment C was 50%, treatment D was 75% and in treatment E, all the water taking out from the tank was 100% replaced by new water from the reservoir, replicated four times. The growth data (heavy and length), with Analysis of Variance (ANOVA) and continueted with Duncan Multiple Range Test.